Two new genera of Oriental xyleborine ambrosia beetles (Coleoptera, Curculionidae: Scolytinae) - Cognato, Anthony I.; Smith, Sarah M.; Beaver, Roger A. (Zootaxa, 2020)
As part of an ongoing revision of the Southeast Asian fauna two distinct species groups were identified and hypothesized as new genera. These species groups were monophyletic as evidenced by a Bayesian analysis of DNA sequences from four genes for 181 xyleborine taxa augmented by 18 species newly included in this phylogenetic analysis. The species groups and newly discovered species demonstrated unique combinations of diagnostic characters and levels of DNA sequence difference commensurable to other xyleborine taxa. Hence, two new genera and three new species were described: Fraudatrix gen. n., Tricosa gen. n., Tricosa cattienensis sp. n., T. indochinensis sp. n., T. jacula sp. n.. The following new combinations are proposed: Fraudatrix cuneiformis (Schedl, 1958) (Xyleborus) comb. n., Fraudatrix melas (Eggers, 1927) comb. n., F. pileatula (Schedl, 1975) (Xyleborus) comb. n., F. simplex (Browne, 1949), (Cryptoxyleborus) comb. n., Tricosa mangoensis (Schedl, 1942) (Xyleborus) comb. n., T. metacuneola (Eggers, 1940) (Xyleborus) comb. n. Keys to the females of the species included in the new genera are presented. Diagnostic characters are given for the genera and species, and the distribution and biology of each taxon is discussed. The addition of these new genera increases the number of recognized genera of Xyleborini to 41.